2022
DOI: 10.3390/ijerph19084914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Risk of Birth Defects Related to the Use of Assisted Reproductive Technology: An Updated Systematic Review

Abstract: Fertility problems constitute a serious medical, social, and demographic problem. With this review, we aim to critically appraise and evaluate the existing literature surrounding the risk of birth defects in offspring conceived using techniques based on assisted reproductive technology (ART). Based on searches of the literature in PubMed and ScienceDirect, we obtained a total of 2,003,275 works related to the topic. Ultimately, 11 original papers published in the last 10 years qualified for inclusion in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] The higher prevalence may be due to the procedures (e.g., altered hormonal environment, culture medium composition, manipulation of gametes) or to the underlying infertility, itself associated with malformations. 2,5,[11][12][13][14][15][16] However, little is known about whether type of infertility influences the prevalence of malformations. In a recent study, polycystic ovary syndrome (PCOS), premature ovarian insufficiency (POI), and endometriosis predicted a higher prevalence of malformations, after accounting for fertility treatment.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] The higher prevalence may be due to the procedures (e.g., altered hormonal environment, culture medium composition, manipulation of gametes) or to the underlying infertility, itself associated with malformations. 2,5,[11][12][13][14][15][16] However, little is known about whether type of infertility influences the prevalence of malformations. In a recent study, polycystic ovary syndrome (PCOS), premature ovarian insufficiency (POI), and endometriosis predicted a higher prevalence of malformations, after accounting for fertility treatment.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Children conceived with assisted reproductive technology (ART) have a higher prevalence of congenital malformations than children conceived without 1–10 . The higher prevalence may be due to the procedures (e.g., altered hormonal environment, culture medium composition, manipulation of gametes) or to the underlying infertility, itself associated with malformations 2,5,11–16 . However, little is known about whether type of infertility influences the prevalence of malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, if regular sexual intercourses within a period of 12 months do not lead to clinical pregnancy, due to impaired spermatogenesis, the infertile couples strongly rely on a positive outcome of assisted reproduction [ 4 , 5 , 6 ]. This term comprises all clinical methods used to assist in gaining pregnancy, amongst which the classic in-vitro fertilization (IVF) has the highest efficiency, attributed to the opportunity for preliminary selection of both female (oocytes) and male (spermatozoa) gametes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, if regular sexual intercourses within a period of 12 months do not lead to clinical pregnancy, due to impaired spermatogenesis, the infertile couples strongly rely on a positive outcome of assisted reproduction [ 4 , 5 , 6 ]. This term comprises all clinical methods used to assist in gaining pregnancy, amongst which the classic in-vitro fertilization (IVF) has the highest efficiency, attributed to the opportunity for preliminary selection of both female (oocytes) and male (spermatozoa) gametes [ 5 ]. Thus, controlled ovarian hyperstimulation can be implemented to increase the number of oocytes available for IVF, while as an integral part of the assisted reproductive technologies, semen processing via gradient density centrifugation and microfluidic sperm-sorting devices, for instance, facilitates the choice of mature spermatozoa [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serafin et al reported that birth defects are not directly related to the use of ART (13). Cardiometabolic risk in children conceived using ART had no significant difference compared to those conceived without treatment (14).…”
Section: Introductionmentioning
confidence: 99%